Angels talking back and new organs of perception: Art-making and intentionality in nature experience. Issue 2 (1st June 2015) - van Boeckel, Jan
This article focuses on the role of the artistic process in connecting to the natural environment. In my research I have explored what participants experience and learn when they engage in different types of arts-based environmental education (AEE) practices that I have facilitated. The premise of AEE is that efforts to learn about our (natural) environment can effectively take their starting point in an artistic activity, usually conducted in groups. I found that, on the whole, two major orientations can be distinguished. One starts from the point of aesthetic sensibility: the tuning in with the senses, or with 'a new organ of perception' (Goethe), in order to perceive 'the more than human' with fresh new eyes. This tradition can be traced back (but is by no means limited) to the Romantic Movement. Art in this context may help to amplify the receptivity of the senses and strengthen a sense of connectedness to the natural world. The other major orientation in seeking bridges between nature and art builds on a view of artistic process as leading to unexpected outcomes and 'emergent properties'. The fundamentally singular experience of making a work of art may evoke an aesthetic object that becomes a 'self-sufficient, spiritually breathing subject' (Kandinsky). The artwork can be spontaneously generative and multilayered with meanings, some of which may even be ambiguous and paradoxical. But perhaps more importantly: it can catch the participant of an AEE activity by surprise, overwhelm him or her as 'coming from behind one's back'. The element of improvisation, of taking in the new and unanticipated and accommodating for it, is the core quality here. These two orientations, when practiced as part of AEE, have implications on how we relate to nature through art. In the closing of this article I address the question of whether it is possible to bridge the dualism between the two orientations.